Effect of miR-124 on PI3K/Akt signal pathway in refractory epilepsy rats - Wang, Ruili; An, Xuelin; Zhao, Shuzhi (Cellular and Molecular Biology, 2020)
This research aimed to investigate the effect of miR-124 on the PI3K/Akt signaling pathway in refractory epilepsy rats. Ten healthy SD rats were selected as a control group, thirty-six successfully established model rats were randomly divided into the model group, mir-124-agomir, mir-124-antagomir, mir-124-agomir+ LY294002 group (combined group), with 9 rats in each group. PI3K or (and) Akt expressions were intervened respectively. The changes in attack latency and cognitive function were observed, and the correlation among miR-124, PI3K, Akt, and attack latency was analyzed. Up-regulation of the level of miR-124 could increase the seizure interval of rats (P< 0.05), improve the cognitive function of rats (P< 0.05), and promote the expression of PI3K, AKT. The level of miR-124, PI3K, Akt was positively correlated with the latent time of seizures in rats, and the level of miR-124 was positively correlated with the level of PI3K, Akt (P< 0.05). In conclusion, miR-124 can play a protective role in temporal lobe epilepsy by promoting PI3K/Akt signaling pathway, including the protection of cognitive function, which may be a potential target for clinical treatment of intractable epilepsy in the future.